Basic Concepts of Digital Da’wah and Digital Counseling: Technological and Spiritual Integrity - Karim, Lia Shofiyatur Rohmah; Sintya Septiana, Zahra (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The development of information and communication technology (ICT) in the modern era has significantly influenced various aspects of life, including religious practices and counseling services. The high penetration of the internet in Indonesia positions the digital space as a strategic medium for delivering Islamic messages and providing online counseling services. Digital da’wah emerges as a transformation of conventional preaching methods into virtual spaces by utilizing social media platforms such as YouTube, Instagram, and TikTok. These platforms are able to reach audiences across generations, particularly the younger generation, although they also face challenges such as the spread of hoaxes, hate speech, and the low level of digital literacy among preachers. Meanwhile, digital counseling has become an innovative form of psychological assistance that offers flexible access, time efficiency, and inclusivity. However, this service also raises issues related to ethics, privacy, and the limitation of human touch, which has traditionally characterized face-to-face counseling. This article aims to describe the basic concepts of digital da’wah and digital counseling by emphasizing the importance of integrating technology with spirituality. The research method employed is library research with a descriptive qualitative approach, analyzing various recent academic sources. The findings indicate that digital da’wah and digital counseling can function effectively when supported by adequate digital literacy, professional competence, and clear ethical regulations. Thus, the integration of technology and spirituality is not merely a trend, but rather a long-term strategy to build a Muslim society that is religious, adaptive, and ready to face the challenges of the digital era.